2024
DOI: 10.24084/repqj02.304
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the Wind-Turbines Under Lightning Strikes Including Nonlinear Grounding System.

Abstract: Windfarms are every day increasing in number. So wind turbines are an easy aim for cloud-to-ground lightning for two main reasons: high isokeraunic level over windfarm locations and the height and sharp of the wind turbine structure and blades. Then the turbine should facility current flowing through its main parts: blades, rotor brushes and tower without dangerous overvoltages. Grounding should be design to derive current efficiently, but in many situations grounding is conditioned to particular location aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Furthermore, it is a rather well affirmed fact that the front duration of the lightning current (among other factors) has a significant influence on the formation of the WT grounding transient potential rise. 5,12 Apart from that, lighting current front duration (in combination with amplitude) has important influence on the so-called back-surge propagation phenomenon, often associated with wind farms. 8 Generally speaking, direct lightning strikes with shorter front duration generate larger overvoltage on the associated equipment, and vice versa.…”
mentioning
confidence: 99%
“…Furthermore, it is a rather well affirmed fact that the front duration of the lightning current (among other factors) has a significant influence on the formation of the WT grounding transient potential rise. 5,12 Apart from that, lighting current front duration (in combination with amplitude) has important influence on the so-called back-surge propagation phenomenon, often associated with wind farms. 8 Generally speaking, direct lightning strikes with shorter front duration generate larger overvoltage on the associated equipment, and vice versa.…”
mentioning
confidence: 99%
“…Although there are a lot of transients studies on the wind farms such as reported in , they did not take into consideration a complete high‐frequency modeling. In , the behavior of the wind turbine under lightning strikes using three models of the grounding system (constant resistance, nonlinear resistance, and frequency‐dependent model) has been studied. The constant resistance is not accurate under lightning surges.…”
Section: Introductionmentioning
confidence: 99%
“…The EMTP-type models for these components, appropriate for the lightning surge analysis, are not readily obtainable. One possible approach to modeling the WT tower-which heavily rests on the existing models of the HV transmission line towers-is presented in [39]. Here tower and blades are represented as simple constant-value and distributed-parameter transmission lines (i.e., the so-called Clark components in EMTP).…”
Section: Wt Tower and Bladesmentioning
confidence: 99%
“…The data needed for these models are sometimes difficult to obtain; the reason for this is that it often consists of several different components, each needed to be appropriately modeled for the lightning surge analysis [15,16,21,[36][37][38][39][40][41]. Moreover, wind farm component models are often frequency-dependent, non-linear or otherwise involve proprietary data belonging to the manufacturers.…”
Section: Issues Related To Emtp Models Of Wind Farm Componentsmentioning
confidence: 99%